Factors impacting COVID-19 vaccine decision making in older adults and people with underlying conditions in Victoria, Australia: A cross-sectional survey. Issue 7 (30th December 2022) - Biezen, Ruby; Kaufman, Jessica; Hoq, Monsurul; Manski-Nankervis, Jo-Anne; Sanci, Lena; Bell, J. Simon; Leask, Julie; Seale, Holly; Munro, Jane; Suryawijaya Ong, Darren; Oliver, Jane; Jos, Carol; et al.
ABSTRACT: Australia's COVID-19 vaccine rollout included prioritizing older adults and those with underlying conditions. However, little was known around the factors impacting their decision to accept the vaccine. This study aimed to assess vaccine intentions, information needs, and preferences of people prioritized to receive the COVID-19 vaccine at the start of the Australian vaccine rollout. A cross-sectional online survey of people aged ≥70 years or 18–69 with chronic or underlying conditions was conducted between 12 February and 26 March 2021 in Victoria, Australia. The World Health Organization Behavioural and Social Drivers of COVID-19 vaccination framework and items informed the survey design and framing of results. Bivariate logistic regression was used to investigate the association between intention to accept a COVID-19 vaccine and demographic characteristics. In total, 1828 eligible people completed the survey. Intention to vaccinate was highest among those ≥70 years (89.6%, n = 824/920) versus those aged 18–69 years (83.8%, n = 761/908), with 91% (n = 1641/1803) of respondents agreeing that getting a COVID-19 vaccine was important to their health. Reported vaccine safety (aOR 1.4, 95% CI 1.1 to 1.8) and efficacy (aOR 1.9, 95% CI 1.5 to 2.3) were associated with intention to accept a COVID-19 vaccine. Concerns around serious illness, long-term effects, and insufficient vaccine testing were factors for not accepting a COVID-19 vaccine. Preferred communication methods included discussion with healthcare providers, with primary care providers identified as the most trusted information source. This study identified factors influencing the prioritized public's COVID-19 vaccine decision-making, including information preferences. These details can support future vaccination rollouts.